Mississippi Blood - Iles, Greg (New York, NY William Morrow, an imprint of HarperCollins Publishers, 2017)
"#1 New York Times Bestselling Author The endgame is at hand for Penn Cage, his family, and the enemies bent on destroying them in this revelatory volume in the epic trilogy set in modern-day Natchez, Mississippi--Greg Iles's epic tale of love and honor, hatred and revenge that explores how the sins of the past continue to haunt the present. Shattered by grief and dreaming of vengeance, Penn Cage sees his family and his world collapsing around him. The woman he loves is gone, his principles have been irrevocably compromised, and his father, once a paragon of the community that Penn leads as mayor, is about to be tried for the murder of a former lover. Most terrifying of all, Dr. Cage seems bent on self-destruction. Despite Penn's experience as a prosecutor in major murder trials, his father has frozen him out of the trial preparations--preferring to risk dying in prison to revealing the truth of the crime to his son. During forty years practicing medicine, Tom Cage made himself the most respected and beloved physician in Natchez, Mississippi. But this revered Southern figure has secrets known only to himself and a handful of others. Among them, Tom has a second son, the product of an 1960s affair with his devoted African American nurse, Viola Turner. It is Viola who has been murdered, and her bitter son--Penn's half-brother--who sets in motion the murder case against his father. The resulting investigation exhumes dangerous ghosts from Mississippi's violent past. In some way that Penn cannot fathom, Viola Turner was a nexus point between his father and the Double Eagles, a savage splinter cell of the KKK. More troubling still, the long-buried secrets shared by Dr. Cage and the former Klansmen may hold the key to the most devastating assassinations of the 1960s. The surviving Double Eagles will stop at nothing to keep their past crimes buried, and with the help of some of the most influential men in the state, they seek to ensure that Dr. Cage either takes the fall for them, or takes his secrets to an early grave. Tom Cage's murder trial sets a terrible clock in motion, and unless Penn can pierce the veil of the past and exonerate his father, his family will be destroyed. Unable to trust anyone around him--not even his own mother--Penn joins forces with Serenity Butler, a famous young black author who has come to Natchez to write about his father's case. Together, Penn and Serenity--a former soldier--battle to crack the Double Eagles and discover the secret history of the Cage family and the South itself, a desperate move that risks the only thing they have left to gamble: their lives. Mississippi Blood is the enthralling conclusion to a breathtaking trilogy seven years in the making--one that has kept readers on the edge of their seats. With piercing insight, narrative prowess, and a masterful ability to blend history and imagination, New York Times bestselling author Greg Iles illuminates the brutal history of the American South in a highly atmospheric and suspenseful novel that delivers the shocking resolution his fans have eagerly awaited"--
"The exhilarating, highly anticipated final volume in the epic trilogy featuring Penn Cage from #1 New York Times bestselling author Greg Iles"--
Publishers Weekly
Booklist
Library Journal
Kirkus Reviews
Adult.
Adult.
Keywords: Mystery fiction; Adventure fiction